Atlas de la grotte Chauvet-Pont d'Arc. Volume 1 - Clottes, Jean; Geneste, Jean-Michel (Documents d'archéologie française, 2020)
From the moment the Chauvet-Pont d'Arc Cave was discovered, in 1994 in Ardèche (France), the art of its walls -attributed to an early phase of the late Paleolithic, around 36,000 years ago- inspired international curiosity and attention. Conscious of the multiple and significant implications of this discovery, the French Ministry of Culture immediately devoted exceptional ressources to the conservation and study of the cave. The Monography de la grotte Chauvet-Pont d'Arc is the official publication of all multidisciplinary and multi-institutional research supported by the Ministry of Culture and conducted in the cave since 1997. The aim of this first volume, the Atlas de la grotte Chauvet-Pont d'Arc is to enable readers to circulate in the cave via the intermediary of a rich iconography, and to observe and understand the underground landscapes in which the cave art and archaeological remains are located. The four parts of the Atlas (methodology, context, floor maps, conservation) are constructed around maps that represent the various data collections, analyses and representations made during the last twenty years of research. An exceptional publication devoted to exceptional multidisciplinary research, the Atlas de la grotte Chauvet-Pont d'Arc offers, in the form of a classic atlas, numerous innovative spatial approaches and concepts: spatial approach to a place of human activity and creativity, spatial approach to an archaeological site, spatial division of a geographic entity of the natural world, which is also a place of collective symbolic espression. » Abundant color illustrations enhance the written presentation of the archaeological remains, including reconstructions based on a digital field model. Finally, the English translation of the figure legends and detailed summaries of each chapter enable international readers clear access to the descriptions, arguments, and interpretations.